[tex]{5}^{x - 3} = \frac{1}{25} [/tex]

1 Answer

  • The first step for solving this is to write the expression on the right side of the equation in exponential form.
    [tex]5^{x-3} = 5^{-2} [/tex]
    Since the bases are the same,, set the exponents equal to each other.
    x - 3 = -2 
    Now move the constant to the right side and then change its sign.
    x = -2 + 3
    Now calculate the sum to get your final answer.
    x = 1
    This means that the correct answer to your equation is going to be x = 1.
    Let me know if you have any further questions.